Emotional capture during emotion-induced blindness is not automatic. (January 2020) - Hoffman, James E.; Kim, Minwoo; Taylor, Matt; Holiday, Kelsey
Abstract: The present research used behavioral and event-related brain potentials (ERP) measures to determine whether emotional capture is automatic in the emotion-induced blindness (EIB) paradigm. The first experiment varied the priority of performing two concurrent tasks: identifying a negative or neutral picture appearing in a rapid serial visual presentation (RSVP) stream of pictures and multiple object tracking (MOT). Results showed that increased attention to the MOT task resulted in decreased accuracy for identifying both negative and neutral target pictures accompanied by decreases in the amplitude of the P3b component. In contrast, the early posterior negativity (EPN) component elicited by negative pictures was unaffected by variations in attention. Similarly, there was a decrement in MOT performance for dual-task versus single task conditions but no effect of picture type (negative vs neutral) on MOT accuracy which isn't consistent with automatic emotional capture of attention. However, the MOT task might simply be insensitive to brief interruptions of attention. The second experiment used a more sensitive reaction time (RT) measure to examine this possibility. Results showed that RT to discriminate a gap appearing in a tracked object was delayed by the simultaneous appearance of to-be-ignored distractor pictures even though MOT performance was once again unaffected by the distractor. Importantly, the RT delay was the same for both negative and neutral distractors suggesting that capture was driven by physical salience rather than emotional salience of the distractors. Despite this lack of emotional capture, the EPN component, which is thought to reflect emotional capture, was still present. We suggest that the EPN doesn't reflect capture but rather downstream effects of attention, including object recognition. These results show that capture by emotional pictures in EIB can be suppressed when attention is engaged in another difficult task. The results have important implications for understanding capture effects in EIB.